Trichomonas vaginalis: underdiagnosis in urban Australia could facilitate re-emergence. Issue 3 (1st November 2009) - Lusk, M Josephine; Naing, Zin; Rayner, Ben; Rismanto, Nikolas; McIver, Christopher J; Cumming, Robert G; McGeechan, Kevin; Rawlinson, William D; Konecny, Pam
Abstract : Objectives: Trichomonas vaginalis (TV) has a low profile in urban sexually transmitted infection (STI) clinics in many developed countries. The objective of this study was to determine the true prevalence of TV in an Australian urban sexual health setting using sensitive molecular diagnostic techniques. Methods: A cross-sectional study investigating the aetiology of cervicitis in women attending two urban sexual health clinics in Sydney, Australia, enrolled 356 consecutive eligible women from 2006 to 2008. The diagnostic yield from the standard clinical practice of discretionary high vaginal wet preparation microscopy in women with suspicious vaginal discharge was compared with universal use of nested PCR for TV of cervical samples. Results: TV was detected by PCR in 17/356 women (4.8%, 95% CI 2.8 to 7.5%), whereas only four cases (1.1%, 95% CI 0.3 to 2.8%) were detected by discretionary wet preparation microscopy. Eleven of the 17 women (p=0.003) were of culturally and linguistically diverse background. Additionally, cervicitis was found to be significantly associated with TV, RR 1.66 (1.14 to 2.42), p=0.034. Conclusions: Traditional TV-detection methods underestimate TV prevalence in urban Australia. The TV prevalence of 4.8% by PCR testing in this study exceeds previously reported urban Australian TV rates of <1%. An increase in trichomoniasis-associated adverse reproductive outcomes and enhanced HIV transmission poses a salient public health threat. Accordingly, TV warrants a higher profile in urban STI clinic settings in developed countries, and we suggest that priority be given to development of standardised molecular TV detection techniques and that these become part of routine STI testing.